Antimicrobial Peptides and Their Assemblies - Ana Maria Carmona-Ribeiro (MDPI AG, 2023)
Antibiotic resistance requires alternatives to fight multi-drug resistant strains. Antimicrobial peptides (AMPs) act by disrupting or solubilizing microbial cell walls or membranes in accordance with mechanisms difficult to counteract from the microbe's point of view. In this review, structure-activity relationships for AMPs and their assemblies are discussed, considering not only their self-assembly but also their interactions with their carriers for optimal delivery or their combinations with other complementary antimicrobials or moieties covalently bound to their chemical structure. The effect of the formulations on AMP activity is also evaluated, revealing a myriad of possibilities. Depending on the interaction forces between the AMP, the carrier, or the elements added to the formulations, AMP activity can be reduced, enhanced, or remain unaffected. Approaches protecting AMPs against proteolysis may also reduce their activity.